Epistemologi Kebijakan Pendidikan Digital: Rekonstruksi Manajemen Pendidikan di Era Kecerdasan Buatan - Mulyana Surya (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2026)
Digital transformation has reshaped educational management through the adoption of learning management systems, educational analytics, and artificial intelligence in decision-making processes. This article examines the relationship between philosophy of science, particularly epistemology, and digital transformation in educational management. Using a conceptual review approach, the study explores positivist, interpretivist, and critical pragmatist perspectives based on the works of Kuhn, Lakatos, and Quine. The findings reveal that digital transformation represents not merely a technical change but also an epistemological shift in how knowledge is constructed, validated, and applied. Excessive reliance on data may lead to reductionism when contextual understanding and ethical considerations are overlooked. Therefore, a multi-epistemological approach and stronger epistemic awareness are essential for developing inclusive, adaptive, and sustainable educational management in the digital era.